2001
DOI: 10.1093/mutage/16.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mutant lymphocytes in cyclophosphamide- and chlorambucil-treated patients

Abstract: Monitoring patients treated with single antineoplastic agents is aiding our understanding of what hazard these drugs pose in vivo. In this study, the frequency of mutant 6-thioguanine-resistant (TG(R)) peripheral blood lymphocytes was monitored before treatment and for < or =35 weeks after treatment of patients with cyclophosphamide (CP) or chlorambucil (CAB). The mean mutant frequency before treatment for six multiple sclerosis patients treated with high-dose CP was 2.53 x 10(-5) and increased after treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…A nitrogen mustard, 1 leads to guanine alkylation and DNA cross-linking, and ultimately prohibits DNA replication and transcription 3233. The primary cellular uptake mechanism of 1 is passive diffusion34 and like many cytotoxics, the lack of nitrogen mustard tumor-specificity contributes to serious side effects 35,36. Thus, improvements have focused upon i) the development of tumor-activated prodrugs – exemplified by the hypoxia-activated N -oxide PX-478 (Figure 1, 2 ) currently in phase I;37 or ii) modifications to engage tumor-specific transport – exemplified by the β- D -glucosyl analog of ifosfamide (glufosfamide, Figure 1, 4 ) which is actively transported into tumor cells by the sodium/ D -glucose cotransporter SGLT3 (SAAT1) 38.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A nitrogen mustard, 1 leads to guanine alkylation and DNA cross-linking, and ultimately prohibits DNA replication and transcription 3233. The primary cellular uptake mechanism of 1 is passive diffusion34 and like many cytotoxics, the lack of nitrogen mustard tumor-specificity contributes to serious side effects 35,36. Thus, improvements have focused upon i) the development of tumor-activated prodrugs – exemplified by the hypoxia-activated N -oxide PX-478 (Figure 1, 2 ) currently in phase I;37 or ii) modifications to engage tumor-specific transport – exemplified by the β- D -glucosyl analog of ifosfamide (glufosfamide, Figure 1, 4 ) which is actively transported into tumor cells by the sodium/ D -glucose cotransporter SGLT3 (SAAT1) 38.…”
Section: Introductionmentioning
confidence: 99%
“…First synthesized over 5 decades ago, chlorambucil remains a current treatment for chronic lymphocytic leukemia (CLL) a Abbreviations: BH 3 ·Et 3 N, borane−triethylamine complex; CLL, chronic lymphocytic leukemia; CNS, central nervous system; DIC, N , N ′-diisopropylcarbodiimide; DMAP, 4-( N ′, N ′-dimethylamino)pyridine; EDAC, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide; GI 50 , growth inhibitory concentration for 50% of the cell population under study; GLUT1, glucose transporter 1; LAH, lithium aluminum hydride; NMM, N -methylmorpholine; SAAT1, sodium/amino acid transporter 1; SGLT3, sodium/glucose transporter 3; SPE, solid phase extraction; THF, tetrahydrofuran. and has served as the basis for newer generation analogues such as the recently approved bendamustine ( 3 ) . A nitrogen mustard, 1 leads to guanine alkylation and DNA cross-linking and ultimately prohibits DNA replication and transcription. , The primary cellular uptake mechanism of 1 is passive diffusion, and like many cytotoxics, the lack of nitrogen mustard tumor-specificity contributes to serious side effects. , Thus, improvements have focused upon (i) the development of tumor-activated prodrugs, exemplified by the hypoxia-activated N -oxide PX-478 (Figure , 2 ) currently in phase I or (ii) modifications to engage tumor-specific transport, exemplified by the β- d -glucosyl analogue of ifosfamide (glufosfamide, Figure , 4 ) which is actively transported into tumor cells by the sodium/ d -glucose cotransporter SGLT3 (SAAT1) . While the specific glycosylation of 1 has presented analogues that display slight improvements in a perceived therapeutic index (slightly improved in vitro potency and subtle reductions of in vivo peripheral toxicity), the analogues synthesized to date have been restricted to the use of d -gluco- or d -galacto-based sugars. …”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic effects of chemotherapeutic drugs (interaction and cross linking with the DNA cells, inhibition of protein or nucleic acid synthesis and DNA‐transcribing enzymes, interferences in replication of genetic material) are known to affect healthy cells as well. Several clinical studies have in fact shown an increase in secondary tumors in patients treated with these substances 1, 2. For this reason, hospital personnel who handle cytostatic drug mixtures are exposed to a risk of adverse health effects.…”
mentioning
confidence: 99%
“…Tumours from NHL patients treated with monoclonal anti-idiotype antibody and chlorambucil have been described with mutated idiotypes (Davis et al, 1998). Point mutations are seen over time in B-cell malignancies (Levy et al, 1987) and use of single antineoplastic agents has been shown to increase lymphocyte mutation frequency in vivo for some patients (Sanderson, Johnson & Henner, 2001). However, in the absence of any follow-up immunofixation to demonstrate the appearance/disappearance of a monoclonal IgM that mirrors the ACA results, this assertion cannot be proven.…”
Section: Discussionmentioning
confidence: 99%